An introduction to Second Temple Judaism : history and religion of the Jews in the time of Nehemiah, the Maccabees, Hillel and Jesus /: history and religion of the Jews in the time of Nehemiah, the Maccabees, Hillel and Jesus. (2010 copyright 2010) - Unknown
No abstract available